EFEKTIVITAS DISIPLIN PEGAWAI TERHADAP PENERAPAN MESIN ABSENSI SIDIK JARI DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA BALIKPAPAN - Hasbullah Helmi; Hartutiningsih .; Achmad Djumlani (Jurnal Administrative Reform, 2017)
The aim of research is to describe and analyze the effectiveness of Employee Discipline Towards Automatic Fingerprint Machine. The focus of this research are: timeliness, adherence to the rules, responsibility and reliability of automatic fingerprint machine. Sources of data taken from the informant and key informants. As the informant was civil servants and non-civil servants, while a key informant was the Head of Department. Analysis of the data that is used in this research is the model developed Interactive of  Miles and Huberman.